1997
DOI: 10.1111/j.1600-0447.1997.tb09655.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and personality features in panic disorder with or without comorbid mood disorders

Abstract: Personality and temperament features, assessed with the Structured Interview for DSM-III-R Personality Disorders-Revised (SIDP-R) and the Tridimensional Personality Questionnaire (TPQ), respectively, were evaluated in 62 patients affected by panic disorder with (PD + MD) (n = 22) or without comorbid mood disorder (PD) (n = 40). A significant difference in the prevalence of personality disorders (PD + MD, 86% vs. PD, 62%; P < 0.05), particularly dependent (PD + DM, 50% vs. PD, 17%; P < 0.01) and borderline (PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…Previous authors reported higher HA scores in patients with UD and comorbid PD than in patients with UD alone or UD comorbid with other Axis I disorders (Ampollini, Marchesi, Signifredi, & Maggini, 1997;Ampollini et al, 1999;Mulder, Joyce, & Cloninger, 1994). However, it is important to point out that, contrary to NS and RD dimensions, which remain stable in patients with UD over time, HA showed to be highly affected by the mood state of the patient.…”
Section: Discussionmentioning
confidence: 71%
“…Previous authors reported higher HA scores in patients with UD and comorbid PD than in patients with UD alone or UD comorbid with other Axis I disorders (Ampollini, Marchesi, Signifredi, & Maggini, 1997;Ampollini et al, 1999;Mulder, Joyce, & Cloninger, 1994). However, it is important to point out that, contrary to NS and RD dimensions, which remain stable in patients with UD over time, HA showed to be highly affected by the mood state of the patient.…”
Section: Discussionmentioning
confidence: 71%
“…Although research has indicated that high harm avoidance and low self-directedness are implicated in vulnerability to depression (Cloninger et al, 2006;Farmer et al, 2003;Richter et al, 2003), similar results have also been found for other psychological disorders (Ampollini, Marchesi, Signifredi, & Maggini, 1997;Loftus, Garno, Jaeger, & Malhotra, 2008;Nery et al, 2008;Sayin, Kuruoglu, Yazici Güleç, & Aslan, 2007). Similarly, EMSs as assessed by the YSQ have been identifi ed in patients with various psychological disorders (Brotchie, Meyer, Copello, Kidney, & Waller, 2004;Delattre et al, 2004;Pinto-Gouveia, Castilho, Galhardo, & Cunha, 2006;Unoka, Tölgyes, & Czobor, 2007;Waller, Dickson, & Ohanian, 2002).…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have proposed an accentuation of some personality traits, including harm avoidance, neuroticism and extraversion, in PD patients with affective comorbidity as compared with those having pure PD (Ampollini et al, 1997;Bienvenu, Nestadt, et al, 2001;Freire et al, 2007). Similarly, Cuijpers et al (2005) found neuroticism to be the trait most strongly related to comorbidity.…”
Section: Neuroticism Extraversion Aggressivenessmentioning
confidence: 84%
“…Additionally, significantly stronger harm avoidance was reported in PD patients with affective comorbidity as compared to those with pure PD (Ampollini, Marchesi, Signifredi, & Maggini, 1997). Taken together, studies to date indicate some alterations in personality profiles of patients with PD, which are more pronounced in the presence of comorbid affective disorders.…”
mentioning
confidence: 94%